Senegalin, a new phenylpropanoid and other secondary metabolites from the stem bark of Ekebergia senegalensis A. Juss. (Meliaceae). Issue 21 (2nd November 2021) - Kemayou, Guy Paulin M.; Happi, Gervais M.; Ngandjui, Yvan Anderson T.; Tchouankeu, Jean Claude; Sewald, Norbert; Ali, Muhammad S.; Kouam, Simeon F.
Abstract: Senegalin (1 ), a new phenylpropanoid has been isolated from the stem bark of Ekebergia senegalensis A. Juss. along with twelve known secondary metabolites including coumarins 2 –5, 4-hydroxy-3, 5-methylbenzoic acid (6 ), pentacyclic triterpenoids 7 –9, acyclic triterpenoids 10 and 11 and steroids 12 and 13, respectively. Their structures were elucidated with the help of spectroscopic techniques including 1 D- and 2 D-NMR. The antibacterial activity of the major compounds (2, 9 –11 ) was evaluated on five bacterial strains. However, only compounds 2 and 11 showed a weak inhibition against Bacillus subtilis and Pseudomonas agarici . Furthermore, the chemotaxonomic significance of these compounds has also been elaborated. GRAPHICAL ABSTRACT: